Scanning Kelvin probe microscopy on bulk heterojunction polymer blends - Maturová, Klára; Kemerink, Martijn; Wienk, Martinus Maria; Charrier, Dimitri S. H.; Janssen, René A. J. (Advanced functional materials, 2009)
Here, correlated AFM and scanning Kelvin probe microscopy measurements with sub-100 nm resolution on the phase-separated active layer of polymer-fullerene (MDMO-PPV:PCBM) bulk heterojunction solar cells in the dark and under illumination are described. Using numerical modeling a fully quantitative explanation for the contrast and shifts of the surface potential in dark and light is provided. Under illumination an excess of photogenerated electrons is present in both the donor and acceptor phases. From the time evolution of the surface potential after switching off the light the contributions of free and trapped electrons can be identified. Based on these measurements the relative 3D energy level shifts of the sample are calculated. Moreover, by comparing devices with fine and coarse phase separation, it is found that the inferior performance of the latter devices is, at least partially, due to poor electron transport.
Gesehen am 16.12.2019